Diplocentrus bicolor sp. n. (Scorpiones: Diplocentridae) from Jalisco, Mexico - Contreras-Félix, Gerardo A.; Santibáñez-López, Carlos E. (Zootaxa, 2011)
Diplocentrus bicolor sp. n. from Huejuquilla el Alto, in northern Jalisco and two nearby localities in Zacatecas is described. It is compared to its geographically closer species from Zacatecas, Aguascalientes and Nayarit. A map with its known distribution is provided.